Acute strongyloides venezuelensis infection did not prevent EAE development: Implications for hygiene hypothesis - Chiuso-Minicucci, F. [UNESP]; Zorzella-Pezavento, S. F. G. [UNESP]; Marra, N. M. [UNESP]; Peres, R. S. [UNESP]; Franca, T. D. G. [UNESP]; Ishikawa, L. L. W. [UNESP]; Rosa, L. C. da [UNESP]; Mimura, L. A. N. [UNESP]; Turato, W. M.; Amarante, A. F. T. do [UNESP]; Sartori, A. [UNESP] (Malaysian Soc Parasitology Tropical Medicine, 2016)
Prevalence of allergic and autoimmune pathologies is clearly increasing in developed countries. This has been attributed to a decreased exposure to certain microorganisms and been referred as hygiene hypothesis. In this study we evaluated if a previous infection with Strongyloides venezuelensis would alter the progression of experimental autoimmune encephalomyelitis (EAE) in Lewis rats. Animals were initially infected with 4000 L3 infective larvae of S. venezuelensis by subcutaneous route. Encephalomyelitis was then induced during the acute phase of the infection by immunization with myelin basic protein emulsified with Complete Freund’s Adjuvant plus Mycobacterium butyricum. Previous infection downmodulated cytokine production but did not change clinical and histopathological EAE manifestations. Cytometric analysis with antibodies specific for CD4+CD25+Foxp3+ regulatory T cells indicated that infection also did not alter the frequency of these cells in spleen and regional lymph nodes. This finding could partly explain the failure of this worm to avoid EAE progression. Altogether these results demonstrated that infection with S. venezuelensis was not able to modify EAE progression in Lewis rats. In the context of the hygiene hypothesis, these results reinforce the necessity of a comparative study among different helminth species to identify the ones with immunoregulatory competence.